The European Portuguese WHOQOL-OLD module and the new facet Family/Family life: reliability and validity studies - Vilar, Manuela (2016)
The aim of this study was to examine the psychometric properties of the European Portuguese version of the World Health Organization Quality of Life-Older Adults Module (WHOQOL-OLD). The European Portuguese WHOQOL-OLD includes a new identified facet, Family/Family life.